Pemberdayaan Masyarakat Melalui Pembangunan Infrastruktur Daerah - Yan Mahameru (Program Studi Pengembangan Masyarakat Islam, 2021)
AbstractThis study aims to seek an understanding of community empowerment through regional infrastructure development using the Literature Review method, namely reading and reviewing main ideas on the same topic to add arguments and views or opinions of the author on the topic to be raised. In addition to researchers using review papers, the authors can also see the advantages and disadvantages of the previous ones, so that they can make improvements and make more regular formulations. At least there are several things we need to do before reviewing a journal article, including: Finding a journal that fits the research topic raised (differentiate a journal from an article or tutorial, Reading the entire contents of the journal, and Trying to rewrite it in your own language the meaning of From this explanation, it can be concluded that a journal review is a text that contains a summary of scientific research on certain topics. This of course can be considered as a summary or evaluation of other people's writings regarding community empowerment through regional infrastructure development. must have guidelines for the impacts and consequences of development planning In order to avoid problems in the development process, another thing is to look at the environmental impacts that will result from development projects initiated primarily at a certain regional level where the area is has characteristics that are still traditional people and are still thick with culture. The development planning process must be able to accommodate the needs of the local community without damaging the existing ecosystem and providing a good effect on the community, especially the economy and welfare.